How earnings announcement impact Faang stock prices? - Magone, André Tiago Torres Lopes (2019)
Beginning in the late '30s, stock market event studies intend to provide more information about market movements and behavior, around the major events during the year, allowing market players to make better and more sustained investment decisions. This paper analyzes how the FAANG stocks behave when quarterly earnings announcement results are reported. To answer this question, we compare the performance of 7 different announcements for each firm, by the calculation of the abnormal returns, using 3 different normal models with 2 different extensions, and test the statistical robustness with 4 different statistical tests. Our results showed different price reactions around events, but consistent high abnormal returns on an individual event and period analysis on the day after the announcement. Results also revealed that on a multi-period analysis, the stocks are not consistently positive or negative, leading to symmetric high abnormal returns and a low percentage of abnormal performance. At the same time, on a multi-event analysis, results, by type of news, show significant under and overreactions on the stock market price movements. However, the efficient market hypothesis is not consistent when the news, resulting from the announcement, incorporate the stock price. From a safety perspective, this study emphasizes on the necessity to consider the impact of quarterly earnings announcement reports, on FAANG stock prices, and consequently on market players’ investment decisions.